METHOD AND SYSTEM FOR RETRIEVING BUILDING AUTOMATION SYSTEM CONTROLLER INFORMATION USING NEAR FIELD COMMUNICATION - SUGUMAR MOHAN; JAIPRAKASH BV (2022)
The invention relates to a method and system for retrieving building automation system controller information using near field communication. A process for retrieving configuration information for a controller of a building automation system (BAS) includes verifying login information on a mobile computing device to ensure the mobile computing device has authority to access a wiring diagram. Then, a mobile computing device receives identity information associated with the controller via Near Field Communication (NFC) read operations from memory of an NFC tag associated with the controller and retrieves, using the identity information, the wiring diagram from a storage medium. The mobile computing device further displays the retrieved wiring diagram associated with the controller. 本发明的主题是"用于使用近场通信检索建筑物自动化系统控制器信息的方法和系统"。一种用于检索用于建筑物自动化系统（BAS）的控制器的配置信息的过程包括验证移动计算装置上的登录信息以确保移动计算装置具有访问布线图的权限。然后，移动计算装置经由近场通信（NFC）读取操作从与控制器相关联的NFC标签的存储器接收与控制器相关联的身份信息，并且使用该身份信息从存储介质检索布线图。移动计算装置还显示与控制器相关联的所检索的布线图。